2010
DOI: 10.1002/btpr.408
|View full text |Cite
|
Sign up to set email alerts
|

The development of a thermostable CiP (Coprinus cinereus peroxidase) through in silico design

Abstract: Protein thermostability is a crucial issue in the practical application of enzymes, such as inorganic synthesis and enzymatic polymerization of phenol derivatives. Much attention has been focused on the enhancement and numerous successes have been achieved through protein engineering methods. Despite fruitful results based on random mutagenesis, it was still necessary to develop a novel strategy that can reduce the time and effort involved in this process. In this study, a rapid and effective strategy is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Protein thermostability is a crucial issue in the practical application of enzymes in dye bioremediation applications. Several studies have reported the application of protein engineering techniques to improve thermal stabilities of peroxidases [68,145,146], azoreductase [147], and laccases [148,149]. In silico design and site-directed mutagenesis of thermo-labile residues of Coprinus cinereus peroxidase (CiP) resulted in two variants (S323Y and E328D) with increased thermostability over the wild-type enzyme in addition to conserved catalytic activity [145].…”
Section: Engineering For Properties Of Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein thermostability is a crucial issue in the practical application of enzymes in dye bioremediation applications. Several studies have reported the application of protein engineering techniques to improve thermal stabilities of peroxidases [68,145,146], azoreductase [147], and laccases [148,149]. In silico design and site-directed mutagenesis of thermo-labile residues of Coprinus cinereus peroxidase (CiP) resulted in two variants (S323Y and E328D) with increased thermostability over the wild-type enzyme in addition to conserved catalytic activity [145].…”
Section: Engineering For Properties Of Enzymesmentioning
confidence: 99%
“…Several studies have reported the application of protein engineering techniques to improve thermal stabilities of peroxidases [68,145,146], azoreductase [147], and laccases [148,149]. In silico design and site-directed mutagenesis of thermo-labile residues of Coprinus cinereus peroxidase (CiP) resulted in two variants (S323Y and E328D) with increased thermostability over the wild-type enzyme in addition to conserved catalytic activity [145]. Similarly, five rounds of mutagenesis/recombination followed by high-throughput screening yielded a variant 1B6, showing 300-fold higher half-life at 50°C than that exhibited by the homodimeric wild-type PpAzoR azoreductase from Pseudomonas putida [147].…”
Section: Engineering For Properties Of Enzymesmentioning
confidence: 99%
“…This peroxidase (CIP) has high activity and broad substrate specificity similar to that of horse radish peroxidase (HRP), although there is less than 10%-16% sequence similarity between CIP and HRP, and thus has attained considerable attention since it was isolated 7,8 . CIP has higher thermostability than HRP 9,10 . It has been used successfully to remove phenolic compounds from wastewater [11][12][13][14][15][16] , to degrade benzene homologs and derivates 17,18 , to decolourate dyes [19][20][21] , and to produce functional polyaromatics [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 97%
“…3236 This is because the biological half-life of a protein is determined by many factors, in addition to the thermostability. For a protein to have a desirably long biological half-life, the protein must be thermostable enough at the body temperature (37°C) to have an in vitro half-life at 37°C which is at least not shorter than the desirable biological half-life.…”
Section: Introductionmentioning
confidence: 99%